Ankyloblepharon filiforme adnatum: case report and literature review - Pereira Vieira, Maria João (2021)
Ankyloblepharon filiforme adnatum (AFA) is a rare condition defined by a partial or complete fusion of eyelids, which can lead to privation amblyopia. A female new born was referred for ophthalmological examination at her fourth day of life due to the presence of bilateral tissue adhesions between upper and lower eyelid. The obstetric history was unremarkable, except for an advanced maternal age. The baby underwent surgical excision of the bands at the level of each eyelid margin, without complications. Neonatal examination of the new born was normal, without systemic alterations or another eye abnormality. Ankyloblepharon filiform adnatum can be associated with systemic syndromes and the treatment should be performed as soon as the diagnosis is done.